2016
DOI: 10.7251/agreng1602088i
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inulin on Calves’ Growth and Possible Reduction of Greenhouse Gas Emission

Abstract: To reduce greenhouse gas emission (GGE) researchers propose to shorten the period of breeding calves of dairy breeds (Mirzaei-Aghsaghali et al., 2015, Fao, 2010. However, producers try to prolong the time of rising animals in order to get more valuable production. The aim of this research was to determine the impact of different dosages of inulin concentrate (50%) produced in Latvia by using special technologies on calves' health, amount of obtained production and to evaluate possible reduction of GGE. Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…The emitted methane was reduced by 30% (Hristov et al, 2015). In other studies, researchers reached the methane reduction by 20%, at the same time, the weight gain increased by additional 75g/day, and milk yield increased by 1l/day in dairy cattle (Bruinenberg et al, 2002;Ilgaza et al, 2016;Nkrumah et al, 2006). It means that with a significant reduction of CH 4 emission the animal productivity can be improved, but we need to find the optimal feeding recipe which would be compatible with conditions and available feed sources in Latvia, taking into account economic factors and the obtained production.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…The emitted methane was reduced by 30% (Hristov et al, 2015). In other studies, researchers reached the methane reduction by 20%, at the same time, the weight gain increased by additional 75g/day, and milk yield increased by 1l/day in dairy cattle (Bruinenberg et al, 2002;Ilgaza et al, 2016;Nkrumah et al, 2006). It means that with a significant reduction of CH 4 emission the animal productivity can be improved, but we need to find the optimal feeding recipe which would be compatible with conditions and available feed sources in Latvia, taking into account economic factors and the obtained production.…”
Section: Introductionmentioning
confidence: 78%
“…But there are fewer studies done about FOS and inulin (both are components of Jerusalem artichoke) and their impact on methane reduction in ruminants (Roonal, 2015), therefore we used inulin for our research. In the previous study by Ilgaza et al (2016), milk supplementation with inulin had very promising results regarding weight gain when animals in the experimental group reached 90kg weight 3 weeks earlier than the control group; also the live weight gain was higher in calves fed with additional supplement of inulin.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Feed additives have the potential to improve nutrient utilization in farm animals by modifying ruminal microbial population and, consequently, ruminal fermentation and digestion (McGuffey, Richardson, & Wilkinson, 2001). Many researchers have found that prebiotics can increase the daily weight gain in calves and have potential to reduce CH 4 production (Mwenya et al, 2004;Hasunuma et al, 2011;Ilgaza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%